Strategi Mitigasi Bencana Tsunami pada Kecamatan Padang Barat, Kota Padang - Ramadhani, Sari; Febriandi, Febriandi (Al-DYAS, 2026)
Padang Barat District is a highly vulnerable area to tsunami hazards, yet it currently lacks a comprehensive spatial analysis–based mitigation strategy. This study aims to (1) map the areas most susceptible to tsunami risk to support mitigation planning in Padang Barat District, Padang City, and (2) analyze effective and applicable tsunami disaster mitigation strategies to minimize potential casualties and damages. A descriptive quantitative approach was employed, utilizing the Weighted Overlay method within a Geographic Information System (GIS) framework for vulnerability mapping, and the Interpretative Structural Modelling (ISM) method for formulating mitigation strategies. The mapping results indicate three levels of tsunami vulnerability: high (38.03%), medium (55.52%), and low (6.44%). ISM analysis identifies the determination of safe evacuation routes as the primary driving factor in effective mitigation. Key contributing factors to high vulnerability include the proximity to coastlines and rivers, low elevation, and relatively flat topography. The study concludes that the development of mitigation strategies must be grounded in spatial vulnerability analysis to enhance community preparedness and reduce potential tsunami impacts. This research provides practical contributions to area-based disaster planning and supports the formulation of mitigation policies in coastal regions.